Twisted Aromatic Frameworks: Readily Exfoliable and Solution‐Processable Two‐Dimensional Conjugated Microporous Polymers. (20th March 2017) - Marco, A. Belen; Cortizo‐Lacalle, Diego; Perez‐Miqueo, Iñigo; Valenti, Giovanni; Boni, Alessandro; Plas, Jan; Strutyński, Karol; De Feyter, Steven; Paolucci, Francesco; Montes, Mario; Khlobystov, Andrei N.; Melle‐Franco, Manuel; et al.
Abstract: Twisted two‐dimensional aromatic frameworks have been prepared by overcrowding the nodes with bulky and rigid substituents. The highly distorted aromatic framework with alternating out‐of‐plane substituents results in diminished interlayer interactions that favor the exfoliation and dispersion of individual layers in organic media.